The Role of International Cooperation in Indonesia’s Maritime Security: Study Case of MT Arman 114 - Manullang, Abel Josafat (Jurnal Lemhannas RI, 2024)
Purpose: This study explores the critical role of Indonesia's maritime domain in national development, focusing on its function as a connector for its archipelagic geography and a repository of natural resources. It highlights biological resources, such as fisheries, and non-biological resources, including natural gas and oil reserves, while emphasising the importance of safeguarding and optimising these assets for sustainable growth. Study Design/Methodology/Approach: The research utilises a qualitative approach, using secondary data from government reports, academic studies, and international maritime frameworks. A thematic analysis examines challenges and opportunities in Indonesia’s maritime security framework, with particular attention to non-state threats and the role of international cooperation. Findings: Indonesia’s vast maritime territory, covering 6.4 million square kilometres, offers significant economic and environmental benefits. However, these benefits face threats from illegal, unreported, and unregulated (IUU) fishing, transnational crimes, and environmental degradation. Limited maritime security resources further hinder effective threat mitigation. Originality/Value: This study highlights the need for a multilateral approach to maritime security challenges. Drawing on the case of the Iranian supertanker MT Arman 114, it underscores the importance of international cooperation and technological advancements in strengthening Indonesia’s maritime security. The research contributes to the broader discourse on maritime security and regional stability in Southeast Asia